A shift in cloze procedure usage: A new tool for activating ZPD - Ajideh, Parviz; Ansarin, Ali Akbar; Mozaffarzadeh, Sorayya (Indonesian Journal of Applied Linguistics, 2020)
Of significant challenges encountered in the field of Foreign Language Acquisition (FLA) is finding efficient procedures to make learning more promising, and at the same time, independent. Along with these attempts, the present study tries to make a shift in the usage of the cloze procedure traditionally used for testing reading comprehension. Our aim was to find out whether using a cloze procedure prior to teaching reading comprehension skills prompts EFL students’ Zone of Proximal Development (ZPD) in learning reading comprehension skills across proficiency levels. To that end, applying quasi-experimental design, 380 B.S. students majoring in engineering were selected based on intact classes and randomly divided into control and experimental groups while their proficiency levels determined through their scores on the Oxford Quick Placement Test. Then, the participants in the experimental group (N=190) received the prepared cloze procedure, whereas those in the control group received the same procedure for teaching reading skills except the cloze before instruction. Both groups received pre-test, post-test, and delayed post-tests. The obtained data were analyzed by SPSS using independent samples t-test to understand the differences between the groups. The results from the tests revealed that using instructional cloze procedure before teaching reading skills has significant effects on participants’ ZPD in all proficiency levels and can broaden their learning. The finding of the present study implies that instead of adhering to the traditional teaching principles and instruments, instructors can use innovative procedures and manipulate traditional methods and tools to facilitate and lengthen learning processes.